1999
DOI: 10.1021/ie980268n
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Neutralization Control Based on Fuzzy Logic:  Experimental Results

Abstract: Many industrial wastes contain acidic or alkaline materials that require neutralization of previous discharge into receiving waters or to chemical and biological treatment plants. The control of the wastewater neutralization process is subjected to several difficulties, such as the highly nonlinear titration curve (with special sensitivity around neutrality), the unknown water composition, the variable buffering capacity of the system, and the changes in input loading. To deal with these problems, this study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition to the non-linearity of the titration curve, other components of the waste change the buffering capacity of the waste water. The controller described by Adroer et al 10 used the fuzzy error, the difference between the desired and actual pH, and the fuzzy change in the error to calculate the change in neutralization flow required to control the pH. As the pH approaches the neutralization point the controller gain must be changed.…”
Section: Applications Of Fuzzy Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the non-linearity of the titration curve, other components of the waste change the buffering capacity of the waste water. The controller described by Adroer et al 10 used the fuzzy error, the difference between the desired and actual pH, and the fuzzy change in the error to calculate the change in neutralization flow required to control the pH. As the pH approaches the neutralization point the controller gain must be changed.…”
Section: Applications Of Fuzzy Logicmentioning
confidence: 99%
“…An alternate scheme would be to use variable width membership functions to increase the control action as the error increases. The tuning element scheme implemented by Adroer et al 10 was found to provide acceptable pH control with a small mixer with a short residence time.…”
Section: Applications Of Fuzzy Logicmentioning
confidence: 99%
“…Qin and Borders demonstrated a three-region fuzzy logic controller (FLC), which requires prior knowledge of the titration curve, for controlling a pH process. Adroer et al proposed a FLC for a laboratory scale neutralization system, The output of the FLC designed is scaled by a parameter which is a function of process output error history, in order to increase robustness of the controller to buffering variations of the feed stream. Effective control of the neutralization process is revealed.…”
Section: Introductionmentioning
confidence: 99%